Nutrient Regulation of Relative Dominance of Cylindrospermopsin-Producing and Non-cylindrospermopsin-Producing Raphidiopsis raciborskii - Lei, Lamei; Lei, Minting; Cheng, Nan; Chen, Zhijiang; Xiao, Lijuan; Han, Bo-ping; Lin, Qiuqi (Frontiers in Microbiology, 2021)
Raphidiopsis raciborskii can produce cylindrospermopsin (CYN) which is of great concern due to its considerable toxicity to human and animals. Its CYN-producing (toxic) and non-CYN-producing (non-toxic) strains co-exist commonly in natural water bodies, while how their relative dominance are regulated has not been addressed. In this study, we combined field investigation and laboratory experiments to assessed the relationship between toxic and non-toxic R. raciborskii abundances and nutrient levels. The rpoC1- and cyrJ-based qPCR was applied for quantifying total and toxic R. raciborskii respectively. The field survey showed that toxic R. raciborskii was detected in 97 of 115 reservoirs where its proportion ranged from 0.3% to 39.7% within the R. raciborskii population. Both total and toxic R. raciborskii abundances increased significantly with trophic level of these reservoirs, consistent with our monoculture and co-culture experiments showing in an increase in R. raciborskii growth with increasing nitrogen (N) or phosphorus (P) concentrations. In the monoculture experiments, growth rates of the non-toxic and toxic strains from Australia or China were not significantly different under the same culture conditions. On the other hand, in the co-culture experiments, the toxic strains displayed a significantly faster growth than non-toxic strains under nutrient replete conditions, resulting in an obvious shift towards the dominance by toxic strains from day 3 to the end of the experiments, regardless of the strain originating from Australia or China. The reverse was found under N or P -limited conditions. Our results indicated that the toxic strains of R. raciborskii have a competitive advantage relative to the non-toxic strains in a more eutrophic world. In parallel to an increase in dominance, both toxic strains grown in the mixed population significantly increased CYN production under nutrient replete conditions as compared to nutrient-limited conditions, suggesting that CYN may be of significance for ecological advantage of toxic R. raciborskii. These results highlight the importance of nutrient availability in regulating abundances and strain dominance of the two genotypes of R. raciborskii. Our findings demonstrated that elevated nutrients would favor the growth of CYN-producing R. raciborskii and CYN production, leading to more blooms with higher toxicity at global scale.